Care burden and associated factors in caregivers of children with cancer - Mahnaz Chaghazardi; Maryam Janatolmakan; Shahab Rezaeian; Alireza Khatony (BMC, 2022)
Abstract Background Evidence suggests that many parents who care for their children with cancer are affected by the care burden due to the chronic nature of the disease. The aim of this study was to determine the burden of care level and its related factors in the caregivers of children with cancer. Method A total of 270 caregivers of children with cancer were included in this cross-sectional study by convenience sampling method. Data collection tools were a personal information form and the Novak & Guest's Caregiver Burden Inventory. Data were analyzed by descriptive and inferential statistics (chi-square and univariate linear regression model). Results The mean ages of caregivers and patients were 35.7 ± 7.0 and 3.1 ± 1.6 years, respectively. The mean care burden was 68.4 ± 1.5 out of 120. About 50 and 36% of caregivers had moderate and severe care burden, respectively. Conclusion Caregivers had moderate to high care burden. A number of factors associated with care burden were identified. Health authorities need to take family-centered measures to reduce the burden of caregivers.